2023
DOI: 10.1541/ieejjia.22007327
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Residential Storage Battery Demand Response in Tertiary Balancing Market

Abstract: Non-memberThe recent increase in residential photovoltaic (PV) power generation has become a major factor in the electricity supply instability. As a result, power balancing at the distribution level is becoming increasingly important. In Japan, storage batteries installed in residential homes along with PV systems has reached nearly 3 GW and are expected to contribute to the power system stability. In this paper, we propose a method for a group of residential consumers to participate in the balancing market b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…[10]. In addition, the previous research on PV systems integrated BESS bidding to the balancing markets can be found, e.g., BESS demand responds in tertiary balancing market based on the past behavior of the consumers, and demand response dispatch optimization [11], and the optimal day‐ahead and intraday market bids via a model predictive control approach considering solar generation prediction [12]. However, only a few studies are related to the absorption of prediction errors by providing headroom in PV without BESS in every time step.…”
Section: Introductionmentioning
confidence: 99%
“…[10]. In addition, the previous research on PV systems integrated BESS bidding to the balancing markets can be found, e.g., BESS demand responds in tertiary balancing market based on the past behavior of the consumers, and demand response dispatch optimization [11], and the optimal day‐ahead and intraday market bids via a model predictive control approach considering solar generation prediction [12]. However, only a few studies are related to the absorption of prediction errors by providing headroom in PV without BESS in every time step.…”
Section: Introductionmentioning
confidence: 99%